2015
DOI: 10.2135/cropsci2014.11.0757
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Induces Black Color and Increases Flavonoid Levels in the Grain of Sorghum Line Tx3362

Abstract: The grain sorghum [Sorghum bicolor (L.) Moench.] line ‘Tx3362’ has a uniformly black pericarp color when produced under summer production conditions and it also contains high levels of 3‐deoxyanthocyanidins (3‐DOAs) in the bran layers of the grain. Consequently, Tx3362 has high levels of antioxidant activity and is a source of natural pigmentation that can be used as natural food coloring. However, prior research indicates that the black color is not fully penetrant in all environments. Specifically, black sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A relatively large number of genes were predicted to be involved with fiber content (Table 8). Fiber could be overshadowed, or overshadowing, total phenolic concentration, as seen in previous reports (Pfeiffer and Rooney, 2015). The specialty compounds of interest are located in the bran layer—the same region where fiber is found in the caryopsis.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…A relatively large number of genes were predicted to be involved with fiber content (Table 8). Fiber could be overshadowed, or overshadowing, total phenolic concentration, as seen in previous reports (Pfeiffer and Rooney, 2015). The specialty compounds of interest are located in the bran layer—the same region where fiber is found in the caryopsis.…”
Section: Discussionsupporting
confidence: 59%
“…This would include grain composition parameters such as fat, protein, and starch composition, but it would not impact estimates of 3‐DOA, phenol, or tannins (Dykes et al, 2014). Pollen flow could not be controlled in this experiment, because shading from pollination bags inhibits the expression of the black pericarp trait (Pfeiffer and Rooney, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent genetic study of black sorghum demonstrated that additional genes (including recessive alleles) beyond the dominant alleles at the R and Y loci function to control the black-grain phenotype. 16 Unlike 3-DOA accumulation in pericarp tissue, 3-DOA production in sorghum leaf tissue is a dominant and common trait irrespective of grain color and is stimulated by pathogen attack or mechanical wounding. 2 Sorghum leaves are characterized as either tan (nonpigmented), red, or purple; a trait referred to as "secondary plant color".…”
Section: ■ Introductionmentioning
confidence: 99%